The Effect of the Presence of Bee Forage on the Existence of the Bee Hives Apis dorsata Binghamii: Pengaruh Keberadaan Tumbuhan Pakan Terhadap Keberadaan Sarang Lebah Hutan Apis dorsata Binghamii - Rosmarlinasiah Rosmarlinasiah; Abigael Kabe; Hafidah Nur; Rian Hidayat; Ahmad Cahyadi (Jurusan Kehutanan -FHIL-UHO, 2024)
Abstract: Sulawesi's endemic bee Apis dorsata Binghamii is a honey producer that needs to be preserved. The research was carried out in Tawanga Village, Uluiwoi District, East Kolaka Regency from June to November 2024. The aim of the research was to determine the types of food trees and nest trees, whether or not the presence of food plants influences the presence of bee hives, and determine the type of habitat preferred (habitat preference). The research method uses a survey method. Vegetation analysis is expressed in absolute and relative values ​​as formulated by Soerianegara and Indrawan (1988). The effect of the presence of food trees on the presence of nests using a completely randomized design (CRD). Data were analyzed using variance (Anova). If Fhit>Ftab H0 is rejected, H1 is accepted, followed by the BNT test (smallest real difference test). Analysis of habitat types preferred by forest bees using the NEU method (Neu et al. 1974). The results of the research showed that there were 44 types of food plants that produce nectar and pollen, 16 hives and bee trees. The most dominant flower-producing types at tree level are: durian (Durio ziberthinus), pole level; Cocoa (Theobroma cacao), and Cashew (Anacardium occidentale), sapling stage of Cocoa (Theobroma cacao), Coffee (Coffea sp) and seedling stage of Coffee (Coffea sp), Tombira (Vitex glabra), and Puloli (Quercus celebica). There is a very significant influence of the changing climate flower season and the dry climate flower season on the weight of beehive honey. The highest average honey yield is found in the dry season. The most preferred habitat preferences of Apis dorsata Binghamii bees; diameter 24.2 - 58.9 cm. Nest height preference 04.26-13.64 m. Preference Height above sea level 78 – 221.5 m above sea level. Air temperature preference is 30.7-36.80C, and air humidity preference is between 36.5-63.75%. Keywords: Apis dorsata Binghamii, bee forage, nest tree, flower season